2015
DOI: 10.1016/j.febslet.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling phototoxicity‐elicited neural dysmorphology and death by insidious function and selective impairment of Ran‐binding protein 2 (Ranbp2)

Abstract: Morphological disintegration of neurons is coupled invariably to neural death. In particular, disruption of outer segments of photoreceptor neurons triggers photoreceptor death regardless of the pathological stressors. We show that Ranbp2−/−::Tg-Ranbp2CLDm mice with mutations in SUMO-binding motif (SBM) of cyclophilin-like domain (CLD) of Ranbp2 expressed in a null Ranbp2 background lack untoward effects in photoreceptors in the absence of light-stress. However, compared to wild type photoreceptors, light-stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…However, mounting physiological and genetic studies support the notion that Ran GTPase-dependent processes regulated by Ranbp2 harbor unique cell type-restricted functions. The cell-type selective functions of Ranbp2 likely stem from the control of nucleocytoplasmic shuttling, proteostasis or post-translational modifications of cell-type selective, stress-elicited or disease-prone substrates, such as hnRNPA2B1, parkin, M-opsin and Stat3, by unrelated domains of Ranbp2 that are interspersed between its RBDs ( Cho et al, 2015a , 2014 ; Patil et al, 2014 ; Um et al, 2006 ; Wälde et al, 2012 ; Hamada et al, 2011 ). This view is also supported by mounting genetic evidence in humans with clinically restricted neurological maladies triggered by selective stressors and mutations in the leucine-rich domain of RANBP2 ( Neilson et al, 2009 ; Wolf et al, 2013 ; Denier et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mounting physiological and genetic studies support the notion that Ran GTPase-dependent processes regulated by Ranbp2 harbor unique cell type-restricted functions. The cell-type selective functions of Ranbp2 likely stem from the control of nucleocytoplasmic shuttling, proteostasis or post-translational modifications of cell-type selective, stress-elicited or disease-prone substrates, such as hnRNPA2B1, parkin, M-opsin and Stat3, by unrelated domains of Ranbp2 that are interspersed between its RBDs ( Cho et al, 2015a , 2014 ; Patil et al, 2014 ; Um et al, 2006 ; Wälde et al, 2012 ; Hamada et al, 2011 ). This view is also supported by mounting genetic evidence in humans with clinically restricted neurological maladies triggered by selective stressors and mutations in the leucine-rich domain of RANBP2 ( Neilson et al, 2009 ; Wolf et al, 2013 ; Denier et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This view is also supported by mounting genetic evidence in humans with clinically restricted neurological maladies triggered by selective stressors and mutations in the leucine-rich domain of RANBP2 ( Neilson et al, 2009 ; Wolf et al, 2013 ; Denier et al, 2014 ). Furthermore, mutations that uncouple selective RBDs of Ranbp2 from Ran GTPase, Ranbp2 haploinsufficiency or mutations impairing the SUMO-binding motif of Ranbp2 promote neural-type restricted phenotypes in the absence or presence of noxious stressors in mice ( Patil et al, 2014 ; Cho et al, 2010 , 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…41 The biologic relevance of the promiscuous binding of argonaute to SUMO-binding motifs of Ranbp2 and other proteins is unknown 41 and such binding contrasts with the physiologic and biologic control of SUMOylated RanGAP, HDAC4 and the ubiquitin-proteasome system by a specific SUMO-binding motif of Ranbp2. 7,17,27 Regardless, we have parenthetically found that loss of Ranbp2 also causes the strong upregulation of pre-miRNA variants of miR-124a in cones 19 and the strong downregulation of miRNAs, such as miR-224 and mi-R200b, in the RPE. 7 Further, the nucleocytoplasmic partition of hnRNPA1 controls the Sterol Regulatory Element-Binding Protein 1a (SREBP-1a)-mediated expression of lipogenic genes implicated in the synthesis of fatty acids, triglycerides and cholesterol.…”
mentioning
confidence: 88%
“…Our prior studies have shown that the age-dependent functions of Ranbp2 are the result of a confluence of activities of various domains of Ranbp2 and partners thereof and aging or environmental stressors. [27][28][29][30] Future studies are needed to parse the molecular bases of the age-dependent activities of Ranbp2.…”
mentioning
confidence: 99%
See 1 more Smart Citation